Popular proverbs and its social functions in the countryside of the Syrian coast (Anthropological Study in the Coastal Village, Baluran) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study reveals an important aspect of the rural cultural heritage of the Syrian coast, and its presence in rural folk proverbs, with its social-economical, moral and esthical functions.The popular proverb is one of the most important elements of popular culture in reflecting the relationship between the individual his environment and his social and cultural surrounding, not only by his ability to convey human experiences, but also by formulating these experiences in an artistic popular language that serves the interactive communicative process and paints a picture of the life of society in the Syrian coastal countryside From all sides.